EXPLORING TEACHING STRATEGIES TO ENHANCE ENGLISH COMMUNICATION SKILLS FOR STUDENTS VOCATIONAL SCHOOL - Marini, Marini Picalasari; Diah Astriyanti; Citra Kusumaningsih (Program Studi Pendidikan Bahasa Inggris, 2025)
This research aims to explore what teaching strategies used by the teachers and the role of schools to enhance English communication skills at vocational schools. Using a qualitative descriptive design, data were collected through semi-structured interview, and documents. The participant of this research are English teachers and headmaster of vocational schools at SMK Negeri 4 Pontianak, SMK Negeri 2 Pontianak, and SMK SMTI Pontianak. The interview was analyzed using thematic analysis and document as supporting the data of interview. The findings of this research indicate that teaching strategies to enhance English communication skills at vocational schools have been implemented, but their implementation has not been consistent. The findings of the study indicate that teaching strategies such as brainstorming, problem-based learning, simulation, large group discussions, role play, and presentations have been used by teachers to improve students' communication skills. However, their implementation has not been consistent across all schools. In addition, the role of schools through policies, programs, and supporting facilities is considered to be less than optimal in meeting students' English communication needs. This study emphasizes the importance of teacher readiness and the role of schools in meeting student needs, which need to be strengthened to encourage more effective and sustainable improvement in English communication skills. Therefore, it is recommended that further research examine teaching strategies that encourage active interaction and contextual communication, as well as evaluate the role of schools in designing consistent policies, programs, and supporting facilities for English communication learning. Keywords: Teaching Strategies, Communication Skills, Students Vocational School.